An Efficient Two-Grid Scheme for the Cahn-Hilliard Equation (Communications in Computational Physics, 2018)
A two-grid method for solving the Cahn-Hilliard equation is proposed inthis paper. This two-grid method consists of two steps. First, solve the Cahn-Hilliardequation with an implicit mixed finite element method on a coarse grid. Second, solvetwo Poisson equations using multigrid methods on a fine grid. This two-grid methodcan also be combined with local mesh refinement to further improve the efficiency. Numericalresults including two and three dimensional cases with linear or quadratic elementsshow that this two-grid method can speed up the existing mixed finite methodwhile keeping the same convergence rate.